2016
DOI: 10.1080/15384101.2016.1234549
|View full text |Cite
|
Sign up to set email alerts
|

Coronin 1B supports RhoA signaling at cell-cell junctions through Myosin II

Abstract: Non-muscle myosin II (NMII) motor proteins are responsible for generating contractile forces inside eukaryotic cells. There is also a growing interest in the capacity for these motor proteins to influence cell signaling through scaffolding, especially in the context of RhoA GTPase signaling. We previously showed that NMIIA accumulation and stability within specific regions of the cell cortex, such as the zonula adherens (ZA), allows the formation of a stable RhoA signaling zone. Now we demonstrate a key role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The heterogeneous changes of actin structures around the extrusion site were found to be coupled with the non-uniform remodeling of CCJ between the extruding cell and its neighbors. Previous studies showed that the reduction of E-cadherin at the junctions, together with a reduction of tension at the lateral membrane, occurs before extrusion [6,11,36]. The reduced tension at the CCJs is necessary for increased contractility that expels the cell [11],…”
Section: A Theoretical Model To Reconcile Forces Produced By Purse-stmentioning
confidence: 99%
“…The heterogeneous changes of actin structures around the extrusion site were found to be coupled with the non-uniform remodeling of CCJ between the extruding cell and its neighbors. Previous studies showed that the reduction of E-cadherin at the junctions, together with a reduction of tension at the lateral membrane, occurs before extrusion [6,11,36]. The reduced tension at the CCJs is necessary for increased contractility that expels the cell [11],…”
Section: A Theoretical Model To Reconcile Forces Produced By Purse-stmentioning
confidence: 99%
“…Recent work has positioned Coronin 1B as the critical actin-binding protein for restructuring perijunctional actin from a branched F-actin network to contractile bundles (Michael et al, 2016). Furthermore, Coronin is required for stabilizing Myosin II at the AJC, which can positively regulate Rho signaling (Michael et al, 2016; Priya et al, 2016). …”
Section: Actin-binding Proteins At Cell-cell Junctions: Organizing F-mentioning
confidence: 99%
“…Further, ROCK was recently found to participate in a feedback network that supported RhoA signaling at cadherin junctions (Priya et al. , 2015, 2016). However, distinct contributions of ROCK1 and ROCK2 to junctional biology have yet to be investigated in detail.…”
Section: Introductionmentioning
confidence: 99%